Extent of Parental School Involvement for Improved Student Performance in Awka South Local Government Area of Anambra State - V. N., Eboatu,; Oluchukwu, Igboka, Doris (European Scientific Journal, ESJ, 2017)
Academic achievement of students does not depend only on school, environmental factors and teacher characteristics, but also on the level of home involvement. This study therefore sought to establish the extent of parental school involvement for students’ improved academic achievement in Awka South Local Government Area of Anambra State. The descriptive survey design was used for this study, with six (6) research questions guiding the study. The population for the study comprised 417 public secondary school teachers from which a sample of 125 teachers using simple random sampling technique. The instrument for data collection was a researcher designed, structured questionnaire which was duly validated by experts in educational management and measurement and evaluation. The questionnaire was tested for reliability using test-retest method. The tool for correlation was the Pearson Product Moment Correlation and this yielded a co-efficient of 0.82. Data collected was analysed using mean and standard deviation statistics to answer the 6 research questions while ANOVA with Friedman’s Test was used to test for significant difference in the six indices of parental involvement. The findings show among others that teachers perceive that parents in Awka South Local Government Area effectively communicate with school and coach their children for improved academic achievement to a moderate extent. There was no significant difference in the teacher’s perception of parental involvement based on the six indices of involvement. Based on the findings, the researchers recommended among others, that parents and the school use social media and other devices to communicate more effectively with the school for improved students’ academic performance.